Eviction of unlawful occupiers in view of City of Johannesburg Metropolitan Municipality v Blue Moonlight Properties (Pty) Ltd 2012 (2) SA 104 (CC) - Brits, Reghard (University of Pretoria, 2020)
Mini Dissertation (LLM)--University of Pretoria,2020.